Comparison of Nanoemulsions and Conservation as a Biopesticide Encapsulation Strategy from Fermentation and Extraction: Review - Astrilia Damayanti; Widya Sari Kusuma Wijayanti; Grandis Belva Ardana; Fera Utnita Sari; Muhamad Reihan Prananda; Sangeetaprivya P. Siva (Universitas Negeri Semarang, 2025)
The increasing demand for sustainable agriculture has accelerated the development of biopesticides as environmentally friendly alternatives to synthetic pesticides. However, their application remains constrained by poor stability, low solubility, rapid degradation, and inconsistent field performance. This review aims to evaluate the relationship between bioactive compound production methods and appropriate encapsulation techniques, focusing on fermentation- and extraction-derived biopesticides. A comparative analysis of recent literature was conducted to assess the compatibility of fermentation and extraction processes with coacervation and nanoemulsion encapsulation technologies. The analysis shows that fermentation-derived bioactive compounds, including microbial spores and protein toxins, are best protected through coacervation, which enhances environmental stability and enables controlled release. Conversely, extraction-derived bioactive compounds, such as essential oils, terpenoids, and phenolics, are more effectively formulated using nanoemulsions, improving solubility, dispersion, bioavailability, and biological efficacy while reducing application rates. Matching bioactive production methods with suitable encapsulation strategies significantly enhances formulation stability, active ingredient delivery, and pest control performance. This integrated approach provides a practical framework for developing effective, stable, and commercially viable biopesticides to support sustainable agricultural systems. This review, based on a comparative analysis of recent studies, highlights that fermentation-derived bioactives are more compatible with coacervation systems, whereas extraction-derived bioactives are better suited for nanoemulsion formulations. The findings emphasise that aligning the characteristics of bioactive sources with suitable encapsulation techniques is crucial for improving stability, active ingredient loading, and pest control performance. This integrated approach provides a strategic framework for designing effective, stable, and commercially viable biopesticide formulations that support sustainable agriculture.